Zveza med analiznimi rezultati - karbonatna bomba in termična analiza - Pogačnik, Željko (Materiali in tehnologije, 2008)
During the following of carbonate rocks reactivity, the geological characteristics like texture and structure must be consider. There are several analyses method in the cement and lime industry, to determinate an amount of CaCO3 during the thermal decomposition of rocks. The most uses the TGA-DTA and XRF and analysis (where the last one cannot give an absolute value of carbonate) in the meantime the petroleum industry swear to carbonate bomb analysis (Müller and Gastner, 1971). In this work I wish to present the comparison results between two analytical methods; acid decomposition and process of thermal decomposition of carbonate minerals. These two analyses are not important only for carbonate determination, during OPC clinker and lime production connected to dissociation of mineral waw material. At the same time they make possible control the amount of consumed heat energy in the process per unit of product. For this purpose we analysed some samples of flyschoid rocks from Anhovo area. The determination results of Mg carbonates with TGA-DTA, XRF, XRD analysis and results of acid decomposition of carbonates by carbonate bomb technique demonstrate a correlation factor of 0.97.
Keywords: karbonati; kemijska analiza; termična analiza